Gerardo Piña Rosales, Carlos E. Paldao y Graciela S. Tomassini (eds.), Rubén Darío y los Estados Unidos, Nueva York, Academia Norteamericana de la Lengua Española, 2017, 279 pp. - Balcells Doménech, José María (Lectura y signo, 2018)
Reseña